A Review on Performance & Emission Characteristics of Diesel Engine Using Different Types of Biodiesel Blends as Alternate Fuel - Niraj N. Raja; Yasin, Sheikh (Asian Review of Mechanical Engineering, 2014)
As a renewable, sustainable and alternative fuel for compression ignition engine, biodiesel instead of diesel has been increasingly fuelled to study its effects on engine performances and emissions in the recent 15 years. Biodiesel is an alternative to petroleum-based fuels derived from vegetable oils, animal fats, and used waste cooking oil including triglycerides. Bio-diesel production is a very modern and technological area for researchers due to the relevance that it is winning everyday because of the increase in the petroleum price and the environmental advantages. Trans esterification is the most common method and leads to monoalkyl esters of vegetable oils and fats, now called bio-diesel when used for fuel purposes. In spite of having some other applications, recently it is being considered as one of the most promising alternative fuels in internal combustion engine. Also on the other hand increasing stringent emission regulation will make the use diesel very difficult in the coming days. Regarding the health and environment there is an alternate of diesel called biodiesel. This review paper collects experimentally investigated records and results of engine performance & emission characteristics of compression engine with biodiesel and compared it with conventional diesel. From the review it is found that the use of biodiesel leads to the substantial reduction in PM, HC and CO emissions accompanying with the imperceptible power loss, the increase in fuel consumption and the increase in NOx emission on conventional diesel engine.